Cultural Leagues – Forerunners of Public Libraries in Serbia - Tamara Malešev; Irena Zečević; Olivera Topalov (Bosniaca, 2020)
The establishment of cultural societies and institutions throughout Serbia after the Balkan wars were one of the priorities of the Kingdom of Serbia. In addition to the Cultural League, there were also Serbian agricultural cooperatives, workers’ and party associations, united in an important mission – education, enlightenment and cultural uplifting of their people. The authors of the paper try to follow the historical development of the Cultural League, whose development and activities have created the conditions for the emergence of public libraries in Serbia.